Palpebra superior coloboma reconstruction using ipsilateral tarsomarginal graft: A case report - Tomie Hermawan Soekamto; Fonny Josh; Muhammad Faruk (Journal of Pediatric Surgery Case Reports, 2021)
Introduction: Coloboma is a congenital abnormality characterized by a defect in the partial or full thickness of the palpebra. Coloboma is a rare condition that can affect either one palpebra or both and requires a surgical approach to correct the aesthetic and functional defects of the palpebra. Case report: An 8-month-old baby presented with coloboma in the palpebra superior of the left eye. The defect size was approximately 12 mm wide and 5 mm in height, located in the middle third of the palpebra superior. The patient's left eye vision was unaffected. The reconstruction procedure was performed using an ipsilateral tarsomarginal graft, which was harvested from the lateral side of the inferior palpebra. Follow-up until two months post-reconstruction showed a good result for the palpebra reconstruction. Following the operation, no cornea exposure was observed with palpebra closure, and a satisfactory aesthetic result was achieved. Conclusion: The use of a tarsomarginal graft for coloboma correction represents a surgical technique with a high success rate, resulting in a good aesthetic appearance, and can be performed during a single operation.